1973
DOI: 10.2170/jjphysiol.23.477
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Pancreozymin as a Determinant of the Exocrine-Endocrine Partition of Pancreatic Enzymes

Abstract: 1. Recent evidence suggests that the pancreatic digestive enzymes are secreted not only into the digestive tract via the gland lumen (exocrine), but also into the blood stream (endocrine). This dual secretion has been designated the 'exocrine-endocrine partition' of enzymes and their precursors, and was investigated in both the isolated and perfused rat pancreas, and the rat pancreas in situ. 2. The release of amylase was accompanied by the release of precursors of proteolytic enzymes either into the common du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Relation between amylase output and concentration of Pz It has been shown that the secretary response varied markedly with the concentration of Pz used: higher concentrations of Pz increased amylase output into the portal vein in contrast to a small increase in the output into the common duct (Saito & Kanno, 1973), and the highest concentration produced a lower output (Debray, Vaille, De La Tour, Rose & Souchard, 1963; Leroi, Morisset & Webster, 1971;F6lsch & Wormsley, 1973; N. Ueda and T. Kanno, unpublished data). As a first approach to confirm the hyperpolarizing effect of Pz, an attempt was made to determine the concentration of Pz that produced the highest and most prolonged amylase output in the isolated and perfused rat pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…Relation between amylase output and concentration of Pz It has been shown that the secretary response varied markedly with the concentration of Pz used: higher concentrations of Pz increased amylase output into the portal vein in contrast to a small increase in the output into the common duct (Saito & Kanno, 1973), and the highest concentration produced a lower output (Debray, Vaille, De La Tour, Rose & Souchard, 1963; Leroi, Morisset & Webster, 1971;F6lsch & Wormsley, 1973; N. Ueda and T. Kanno, unpublished data). As a first approach to confirm the hyperpolarizing effect of Pz, an attempt was made to determine the concentration of Pz that produced the highest and most prolonged amylase output in the isolated and perfused rat pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the former possibility, cholinergic stimulation and the peptide hormone cholecystokinin-pancreozymin can greatly augment the basolateral flux of amylase (7-10, 12, 13). This flux may be quite large and has been estimated to account for as much as 20% ofmaximal duct-directed secretion under certain circumstances (7,8,10,12,13 3-hr period and a proportional increase in degradative rate (10-fold), then there would also be a 10-fold increase in amylase activity in the gut. Thus, in order to explain the absence of such an increase in terms of degradation, degradation would have to have been enhanced to a substantially greater degree than secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The first is that digestive enzymes can be reabsorbed intact although not necessarily in unaltered chemical form (1)(2)(3)(4)(5)(6) and that, at least after several hours of highly augmented secretion, enzyme appears to be conserved in this fashion (2). The second is that there is a substantial flux of at least some digestive enzymes from pancreas to blood-an endocrine secretion that can be greatly enhanced by natural secretagogues and that has been shown to be capable of rates as large as 10-20% of maximal duct-directed secretion (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The other five rats were perfused in the same way but adding pancreozymin (PZ, Eizai, Japan) to the perfusate in a concentration of 1.5 C.H.R.u/ml. Since it is reported that the activity of certain pancreatic enzymes in the portal vein reaches the maximum level when PZ is infused into the blood vessels of the rat in a concentration of 1.5 C.H.R.u/ml (SAITO and KANNO, 1973), this dose of PZ was used in the present study. Subsequently, each animal was again perfused with 70-80ml of paraformaldehyde/glutaraldehyde (PA/GA) fixative for 5-8min.…”
Section: Methodsmentioning
confidence: 99%
“…However, the transport mechanism and pathways of the enzymes from the acinar cell into the blood stream remain obscure. Of particular interest for morphologists is the report described by some physiologists (SAITO and KANNO, 1973), who suggested that the pancreatic enzymes are first secreted into the lumen from the apical cytoplasm of the acinar cells (PALADE, 1975), and then, take the passage into blood vessels by passing through the intercellular spaces between acinar cells when a high concentration of pancreozymin is present.…”
mentioning
confidence: 99%